Partial loss of GATA factor Pannier impairs adult heart function in Drosophila - Qian, Li (Oxford University Press, 2009)
The GATA transcription factor encoded by pannier (pnr) is a critical regulator of heart progenitor formation in Drosophila. Mutations in GATA4, the mammalian homolog of pnr, have also been implicated in causing human cardiac disease in a haploinsufficient manner. Mouse models of Gata4 loss-of-function and gain-of-function studies underscored the importance of Gata4 in regulating cardiac progenitor cells specification and differentiation. However, it is not known whether pnr/Gata4 is directly involved in establishing and maintaining adult heart physiology because of the lethality associated with defective heart function and redundancy among various GATA factors in vertebrates. Here, we took advantage of the Drosophila heart model to examine the function of pnr in adult heart physiology. We found that pnr heterozygous mutants result in defective cardiac performance in response to electrical pacing of the heart as well as in elevated arrhythmias. Adult-specific disruption of pnr function using a dominant-negative form pnrEnR revealed a cardiac autonomous requirement of pnr in regulating heart physiology. Moreover, we identified Tbx20/neuromancer (nmr) as a potential downstream mediator of pnr in regulating cardiac performance and rhythm regularity, based on the observation that overexpression of nmr genes, but not of tinman, partially rescues the adult defects in pnr mutants. We conclude that pnr is not only essential for early cardiac progenitor formation, along with tinman and T-box factors, but also plays an important role in establishing and/or maintaining proper heart function, which is partially through another key regulator Tbx20/nmr.